Analysis of Implementation of the Bandwagon Effect to Build and Sustain A Business - Yashinta Putri Dwi Astuti; Deva Nita Mulya; Aldian Umbu Tamu Ama; Ignatius Bias Galih Prasadhya (Jurnal Mantik, 2022)
Nowadays, internet developments can be adopted to increase a business through deployment information, thus stimulating the effect of following the news. The following phenomenon or trend is called the bandwagon effect and can be used to build a business by utilizing the trends. At this time, one of the trends is the rise of the viral culinary idea. Nielsen reported that foods are on the first rank in the contribution of consumer spending. So opening a culinary business is an opportunity. The method used is qualitative descriptive. The data resources were obtained from primary data through in-depth interviews with Sobat Ngelak. This research found that when used well, the bandwagon effect will be a good business opportunity. However, the bandwagon effect can not last long without being balanced with opportunity recognition. Ability to analyse an opportunity and create an idea required as a consequence of Sobat Ngelak to follow the trend on social media. The bandwagon effect has the benefit to give of contributing to increasing the demand of the market.